2021
DOI: 10.3390/mi12080940
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Local Concentration and Viscosity Distribution during Glycerol-Water Mixing in a Y-Shape Minichannel: A Proof-of-Concept-Study

Abstract: The work presents an efficient and non-invasive method to visualize the local concentration and viscosity distribution of two miscible and non-reacting substances with a significant viscosity difference in a microchannel with a Y-shape cell. The proof-of-concept setup consists of a near-infrared (NIR) camera and cost-effective dome lighting with NIR light-emitting diodes (LED) covering the wavelength range of 1050 to 1650 nm. Absorption differences of glycerol and water and their mixtures with a mass fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has recently been shown that microscopic pockets of different glycerol concentration (and viscosity) can form during the mixing of glycerol and water. [ 29 ] The persistence of these domains can be explained by comparatively slow movement of glycerol molecules between distinct domains of more water‐rich regions. [ 30 ] Nakagawa and Oyama concluded that, due to difference in H‐bond strength, water in water–glycerol mixtures can move faster than in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown that microscopic pockets of different glycerol concentration (and viscosity) can form during the mixing of glycerol and water. [ 29 ] The persistence of these domains can be explained by comparatively slow movement of glycerol molecules between distinct domains of more water‐rich regions. [ 30 ] Nakagawa and Oyama concluded that, due to difference in H‐bond strength, water in water–glycerol mixtures can move faster than in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Using optical procedures, fluorescence and near-infrared absorption spectroscopy or imaging are the dominant effects for determination of film thickness [4,13]. The fluorescence approach provides access to the local film thickness if any fluorescent material is available or added to the liquids, thus altering the composition of the liquid stream.…”
Section: Local Film Thicknessmentioning
confidence: 99%
“…Such 2D approaches as ultraviolet-visible (UV/VIS), fluorescence and near-infrared imaging provide local, molecule-sensitive and non-contact concentrations. Every 2D measurement point is a mean value over the local film thickness [4,15].…”
Section: Concentration Measurements On Trickle and Falling Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina et al determined the local concentration and viscosity of glycerol/water mixtures in microchannels with near-infrared imaging using a near-infrared camera and LEDs in this range [69].…”
Section: Introductionmentioning
confidence: 99%